Perencanaan Pendidikan Agama Islam Kontemporer - Aminuddin Aminuddin; Kamaliah Kamaliah (Al-Aulia: Jurnal Pendidikan dan Ilmu-Ilmu Keislaman, 2022)
Education is a process of experience, because life is a growth education means helping inner growth without being limited by humans. Humans as creatures who are given advantages by Allah SWT with a form of reason in humans that other creatures of Allah do not have in their lives, that to cultivate their minds requires a pattern of education through a learning process. Planning is a projection of what is needed in order to achieve valid and valuable goals in educational institutions. Contemporary Islamic Education is an activity that is carried out in a planned and systematic way to develop the potential of students based on the principles of Islam at this time. Education is one of the basic needs in human life who thinks how to live the life of this world in order to maintain life and the livelihood of humans who carry out the task of the Kholiq to worship.